Inclusion: conceptions of teachers of the Secretariat of Education of the State of Sao Paulo - Silveira Bello, Marcia Miranda [UNESP]; Messias Fialho Capellini, Vera Lucia [UNESP]; Garcia Ribeiro, Job Antonio (Univ Federal Santa Maria, 2017)
Recently, respecting differences and promoting inclusion are frequent topics in a wide range of research, including education. In this context, the term inclusion has assumed multiple approaches giving rise to different educational practices by those who intend to concretize it. The objective of the present work was to analyze the understanding that state teachers of education of Sao Paulo have about this concept. The data were collected through narratives elaborated by the subjects during a continuing training course offered through the Programa Rede Sao Paulo de Formacao Docente (REDEFOR). The main results point to the need to overcome a homogenizing view of education, which considers that only the students with disabilities are different from the others, and in which school inclusion would only be for this public.
Keywords: REDEFOR; Continuing education; School inclusion